Out-of-phase relationship of Holocene moisture variations between the northeastern and southeastern Tibetan plateau and its societal impacts - Duo Wu; Minmin Ma; Yongxiu Lu; Shilong Guo; Tao Wang; Xuyi Ma; Guanghui Dong (Fundamental Research, 2025)
It is widely accepted that Holocene climatic and environmental changes had major impacts on socioeconomic development and the evolution of civilization. The eastern margin of the Tibetan plateau (TP) has been an important passageway for south‒north migration of agricultural groups since the late Neolithic. Prehistoric farmers began to occupy the northeastern Tibetan plateau (NETP) and the area of modern Yunnan Province (YNP), on the southeastern margin of the TP, from ∼5200 BP and ∼4600 BP, respectively. This occupation was potentially closely linked to climatic and environmental changes; however, the spatiotemporal pattern of moisture variations between these two regions, and its possible impact on human settlement and the migration of farming communities along the eastern margin of the TP during the late Neolithic and Bronze Age, are unclear. In the present study, well-dated sedimentary records with unambiguous indicators of humidity variations from the NETP and YNP were integrated, along with radiocarbon dates from human and animal bones and the remains of crop plants from archaeological sites in this region. The results indicate a long-term, out-of-phase relationship of moisture variations between the NETP and YNP during the middle to late Holocene. A mid-late Holocene increase in humidity on the NETP facilitated the development of agropastoral societies during the period of ∼5200‒2200 BP. However, pronounced cooling from ∼5000 BP forced the southward dispersal of millet farming groups along the eastern margin of the TP during the fifth millennium BP. Decreasing moisture in YNP promoted the expansion of an open landscape, which affected the development of agriculture during the period of ∼4600‒2200 BP. Our results suggest that changes in moisture affected the development of prehistoric agriculture in the northeastern and southeastern marginal areas of the TP in different ways, implying that the development of prehistoric human society largely depended on the regional climatic conditions.